Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có
\(5x=-3y=4z\)
\(\Rightarrow\frac{x}{12}=-\frac{y}{20}=\frac{z}{15}\)
\(\Rightarrow\frac{x}{12}=-\frac{y}{20}=\frac{3z}{45}=\frac{x-y+3z}{12+20+45}=\frac{7}{77}=\frac{1}{11}\)
\(\Rightarrow\hept{\begin{cases}x=\frac{1}{11}.12=\frac{12}{11}\\-y=\frac{1}{11}.20=\frac{20}{11}\\3z=\frac{1}{11}.45=\frac{45}{11}\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=\frac{12}{11}\\y=-\frac{20}{11}\\z=\frac{45}{11}:3=\frac{15}{11}\end{cases}}\)
Vậy \(\hept{\begin{cases}x=\frac{12}{11}\\y=\frac{-20}{11}\\z=\frac{15}{11}\end{cases}}\)
a) \(\left(x-3\right)^2-4=0\)
\(\left(x-3\right)^2=0+4\)
\(\left(x-3\right)^2=4\)
\(\left(x-3\right)^2=\pm4\)
\(\left(x-3\right)^2=\pm2^2\)
\(\orbr{\begin{cases}x-3=2\\x-3=-2\end{cases}}\)
\(\orbr{\begin{cases}x=5\\x=1\end{cases}}\)
b) \(\left(2x+3\right)^2-\left(2x+1\right)\left(2x-1\right)=22\)
\(4x^2+12x+9-4x^2+1=22\)
\(12x+10=22\)
\(12x=22-10\)
\(12x=12\)
\(x=1\)
c) \(\left(4x+3\right)\left(4x-3\right)-\left(4x-5\right)^2=16\)
\(16x^2-9-16x^2+40x-25=16\)
\(-34+40x=16\)
\(40x=16+34\)
\(40x=50\)
\(x=\frac{50}{40}=\frac{5}{4}\)
d) \(x^3-9x^2+27x-27=-8\)
\(x^3-9x^2+27x-27+8=0\)
\(x^3-9x^2+27x-19=0\)
\(\left(x^2-8x+19\right)\left(x-1\right)=0\)
Vì \(\left(x^2-8x+19\right)>0\) nên:
\(x-1=0\)
\(x=1\)
e) \(\left(x+1\right)^3-x^2\left(x+3\right)=2\)
\(x^3+2x^2+x+x^2+2x+1-x^2-3x^2=2\)
\(3x+1=2\)
\(3x=2-1\)
\(3x=1\)
\(x=\frac{1}{3}\)
b) \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x-3\right)\left(x+3\right)=8\)
\(\Rightarrow x^3-1-x\left(x^2-9\right)=8\)
\(\Rightarrow x^3-1-x^3+9x=8\)
\(\Rightarrow9x=9\Rightarrow x=1\)
c) \(\left(x^2+2\right)\left(x-4\right)-\left(x+2\right)\left(x^2+4x+4\right)=-16\)
\(\Rightarrow x^3-4x^2+2x-8-\left(x+2\right)\left(x+2\right)^2=-16\)
\(\Rightarrow x^3-4x^2+2x-8-\left(x+2\right)^3=-16\)
\(\Rightarrow x^3-4x^2+2x-8-\left(x^3+6x^2+12x+8\right)=-16\)
\(\Rightarrow x^3-4x^2+2x-8-x^3-6x^2-12x-8=-16\)
\(\Rightarrow-10x^2-10x-16=-16\)
\(\Rightarrow10x^2+10x=0\)
\(\Rightarrow10x\left(x+1\right)=0\Rightarrow\left[{}\begin{matrix}x=0\\x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=-1\end{matrix}\right.\)
a: \(=\dfrac{4x^3+8x^2-11x+3-\left(x^2-5\right)\left(2x-1\right)-2x^3-5x^2+x+1}{\left(2x-1\right)^3}\)
\(=\dfrac{2x^3+3x^2-10x+4-2x^3+x^2+10x-5}{\left(2x-1\right)^3}\)
\(=\dfrac{4x^2-1}{\left(2x-1\right)^3}=\dfrac{2x+1}{\left(2x-1\right)^2}\)
b: \(=\dfrac{1+x+1-x}{1-x^2}+\dfrac{2}{1+x^2}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{2+2x^2+2-2x^2}{1-x^4}+\dfrac{4}{1+x^4}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{4+4x^4+4-4x^4}{1-x^8}+\dfrac{8}{1+x^8}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{8+8x^8+8-8x^8}{1-x^{16}}+\dfrac{16}{1+x^{16}}\)
\(=\dfrac{32}{1+x^{32}}\)
khai triển rồi rút gọn ta tính được: 8x+24=16 => 8x=-8=> x=-1
\(x\).(\(x^2\) + 4\(x\) - 4) - 8.(\(\dfrac{1}{8}\)\(x^3\) + \(\dfrac{1}{2}\)\(x^2\) - \(\dfrac{3}{2}\)\(x\) - 3) = 16
\(x^3\) + 4\(x^2\) - 4\(x\) - \(x^3\) - 4\(x^2\) +12\(x\) + 24 = 16
(\(x^3\) - \(x^3\)) + (4\(x^2\) - 4\(x^{^{ }2}\)) + (12\(x-4x\)) = 16 - 24
0 + 0 +8\(x\) = - 8
8\(x\) = - \(\dfrac{8}{8}\)
\(x\) = -1
Vậy \(x=-1\)